Systems of systems - Luzeaux, Dominique; Ruault, Jean-Rene (London : Wiley, 2010)
The book offers a comprehensive exploration of systems of systems, providing a multidisciplinary perspective and addressing key aspects of their engineering and management. It delves into the concept, practical illustrations, and engineering methods associated with these complex systems. The first part introduces the notion of a system of systems, comparing different definitions and providing practical examples. It answers fundamental questions about what a system of systems is and how its complexity can be effectively managed. The second part focuses on the engineering and modeling aspects of systems of systems, addressing critical steps such as stakeholder needs elicitation, architecture optimization, integration, qualification, and utilization. It also highlights the importance of standardization in dealing with these complex systems. Overall, the book provides valuable insights and guidance for researchers, practitioners, and students interested in understanding and managing systems of systems.
Includes index.
Keywords: Defining systems of systems; Systems of systems engineering; Architecture optimization